The Comparison Between Using English Grammar Book And Using Internet As A Media On The Students’ Ability In Mastering Past Participle At Mts N 2 Medan - Siti Zubaidah (VISION, 2018)
This research was aimed to know the comparison between using English grammar book and using Internet as a media on the students’ ability in mastering past participle at MTs N 2 Medan. The population of this research was the second year students of MTs N 2 Medan. The population consists of ten classes and the total number of the population was 392 students. The researcher used cluster sampling to get the sample. The sample consist of 87 students, which consist of VIII1 44 students that taught by using English grammar book as media and VIII5 43 Students that taught by using Internet as media. This research quantitative approach and the technique of collecting data used t-test formula. The result of the research showed that the comparison between using English grammar book and using Internet as a media on the students’ ability in mastering past participle can be described as below: the average score of the students’ ability which taught by using English grammar book as a media = 85 with the highest score =100 and the lowest score = 50 and the average score of the students’ ability which taught by using Internet as a media = 90.2 with the highest score = 100 and the lowest score = 60. Based on the statistical computation of t-test formula, found the coefficient = 2.31whereas the value of ttable = 1.66. It was indicated that there was the comparison between using English grammar book and using Internet as a media on the students’ ability in mastering past participle at MTs N 2 Medan. It showed that the teaching learning process by using Internet was more effective to increase the students’ ability in mastering past participle at MTs N 2 Medan.